THE TEMPLE ART OF ODISHA: A STUDY OF THE ARTIST AND CRAFT ORGANIZATION - Ujwala Kumar Mohanandia (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
In India, monuments are frequently categorised according to the dynasty that ruled at the time they were constructed. Compared to other regions, Odisha is unique in that its temple art has a steady and continuous development that appears to have been unaffected by the numerous kingdoms that ruled the territory1.The aforementioned remark implies the existence of a strong architectural legacy and the continuation of a tradition of temple sculptors and architects in accordance with a recognised standard. Over 700 years, from the 6th century CE to the 13th century CE, Odisha saw a constant human endeavour in the field of temple construction, which has yielded common characteristics. The Odishan School, also known as Kalingan School, of temple art was in full swing due to the huge religious and cultural resurrection that started with the political period of Sailodbhavas, gained momentum under the Bhaumakaras and Somavamsis, and peaked during the Ganga period. Even under the Suryavamsi-Gajapatis, however, the activities continued, albeit very little and at a subsistence level. From Parasuramesvara (Fig.1) to the Lingaraj (Fig.2) temples at Bhubaneswar, to the massive Sun temple at Konark, the art of Odisha’s temples shows a definite evolutionary trend for the observant observer.